POTENSI BAKTERI ANTAGONIS DALAM MENEKAN PERKEMBANGAN PENYAKIT LAYU BAKTERI JAHE - KARDEN MULYA; SUPRIADI SUPRIADI; ESTHER M. ADHI; SRI RAHAYU; NURI KARYANI (Pusat Penelitian dan Pengembangan Perkebunan, 2000)
Potency of antagonist bacteria in inhibiting the bacterial wilt disease progress gingerBacterial wilt disease caused by Pseudomonas solanacearum is an important disease in ginger plant (Zingiber oicinale Rose.) in Indonesia. The objective of this research was to study the effectiveness of biological agents in inhibiting the progess of bacterial wilt on ginger. The research was conducted at the geenhouse of Research Institute for Spice and Medicinal Crops in 1997-1998 then was followed with a ield experiment at Sukamulya Experimental Garden in 1998/1999. At the greenhouse experiment seven kinds of antagonists bacteria were formulated either individually or combination. Pseudomonas fluorescens (PF), P. cepacia (PC) and Bacillus sp. (BC), mixtue of PF + PC, mixtue of PC + BC, mixture of PF + BC, and mixtue of PF + PC + BC were tested in the geenhouse on ginger plant cultivars putih besar grown in the pot containing soil formerly used for growing P. solanacearum infected tomato. I he results of this experiment indicated that the combination of PF+PC+BC significantly suppressed the progress of bacterial wilt disease compaed to control and other tested combination. In the ield experiment carried out at the bacterial wilt disease endemic area the combinations of PF+PC+BC, Trichoderma harzianum (Bit-1) and combination of PF+PC+BC+BII-I were tested with two levels of application, i.e. two applications with two months interval and 4 application with one month interval. The results showed that the application of antagonists bacteria inhibited Ihe bacterial wilt disease progress and signiicantly increased ginger rhizome yield. The yield of the rhizome from the plants teated with different intervals were not different. However, the application of the antagonist bacteria were not able to eradicate ginger infection by Pseudomonas solanacearum thoroughly.